Superstring theory on AdS2 × S2 as a coset supermanifold - Berkovits, N. [UNESP]; Bershadsky, M.; Hauer, T.; Zhukov, S.; Zwiebach, B. (Elsevier B.V., 2000)
We quantize the superstring on the AdS2 × S2 background with Ramond-Ramond flux using a PSU(1,1\2)/U(1) × U(1) sigma model with a WZ term. One-loop conformal invariance of the model is guaranteed by a general mechanism which holds for coset spaces G/H where G is Ricci-flat and H is the invariant locus of a ℤ4 automorphism of G. This mechanism gives conformal theories for the PSU(1,1\2) × PSU(2\2)/SU(2) × SU(2) and PSU(2,2\4)/SO(4,1) × SO(5) coset spaces, suggesting our results might be useful for quantizing the superstring on AdS3 × S3 and AdS5 × S5 backgrounds. © 2000 Elsevier Science B.V. All rights reserved.